2019
DOI: 10.5935/abc.20190067
|View full text |Cite|
|
Sign up to set email alerts
|

The Olympic Experimental Gymnasium Program and its Association with the Prevalence of Cardiovascular Risk Factors in Adolescents: A Cross-Sectional Study

Abstract: Background Cardiovascular disease (CVD) is the leading cause of death worldwide. Physical activity (PA) and appropriate diet, if adopted in childhood and adolescence, may reduce the CVD burden in later life. The Olympic Experimental Gymnasium (OEG) project was implemented to increase the PA levels of students by means of regular physical exercise and healthy eating habits. Objectives To estimate and compare the prevalence of CVD risk factors in OEG schools versus regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It was found that students' knowledge of "concept of CVD (58.12%)" and "factors affecting CVD" (52.17%) was inadequate, which may be due to the fact that students did not receive adequate education on the importance and risk factors of CVD (19). In addition, the knowledge of "behaviors causing overweight and obesity (90.62%)" and "hazards of snacks and milk tea (89.45%)" was better, but there was insufficient knowledge of "hazards of prolonged sedentary behavior (22.92%)" and "definition of BP in adolescents (6.83%)" probably because of the imbalance in the transmission of health information.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that students' knowledge of "concept of CVD (58.12%)" and "factors affecting CVD" (52.17%) was inadequate, which may be due to the fact that students did not receive adequate education on the importance and risk factors of CVD (19). In addition, the knowledge of "behaviors causing overweight and obesity (90.62%)" and "hazards of snacks and milk tea (89.45%)" was better, but there was insufficient knowledge of "hazards of prolonged sedentary behavior (22.92%)" and "definition of BP in adolescents (6.83%)" probably because of the imbalance in the transmission of health information.…”
Section: Discussionmentioning
confidence: 99%